Ersättningsteologins historiska bakgrund - Svartvik, Jesper (Nordisk judaistik, 1998)
Christian replacement theology (RT) is in this article defined as the notion that Judaism has been a good and true religion, but that it eventually ceased to bear those characteristic features and therefore was replaced by Christianity. Christianity is thus everything Judaism has been, probably even more. The New Testament letter to the Hebrews is analysed, especially its usage of the Septuagint. The RT in Heb, is dependent on the Greek version of Jeremiah, which differs considerably from the Hebrew Masoretic text. The letter of Barnabas - which belongs to the Apostolic Fathers - is also examined. There is reason to believe that Barn was written due to plans of rebuilding the temple in Jerusalem. The overarching theological structure in Barn should thus be understood in relation to this fundamental attitude. By way of conclusion the article presents five serious flaws in RT: 1) development is not the same as replacement, 2) the RT petrifies the state of things at the time of the so-called replacement, 3) those who replace others will soon find themselves to be replaced, 4) the RT is a manifestation of a manipulation of history. It is thus a flawed historiography and, finally, 5) the RT is ultimately nothing but escapism.